Comparison of bupivacaine and levobupivacaine for treatment of post-thoracotomy pain through thoracic paravertebral block - Kaya, Sener; Basagan Mogol, Elif; Kaya, Fatma Nur; Bayram, Ahmet Sami; Turker, Gurkan; Yilmaz, Canan; Karasu, Derya (The European Research Journal, 2016)
Objectives. The aim of this study was to compare postoperative pain and respiratory functions of lobectomy patients who were given bupivacaine or levobupivacaine with fentanyl through a paravertebral catheter.Methods. ASA I-II patients (n=40, 18-65 years old) randomized into two groups. While Group B was administered 0.25% bupivacaine with fentanyl, Group L was administered 0.25% levobupivacaine with fentanyl at a rate of 0.1 ml/kg/hr through paravertebral catheter for patient controlled analgesia. Visual analog scale (VAS), arterial blood gases and respiratory function tests were assessed.Results. There were no significant differences in terms of demographic characteristics and surgery durations between the groups (p>0.05). VAS scores recorded at the 1st postoperative hour were higher in both groups compared to the following hours (p